Pengaruh Kualitas Pelayanan dan Harga terhadap Loyalitas Konsumen pada Harmony Hairstyle Stabat Kabupaten Langkat - Adeck Syaifullah Ahmad; Ulen Bangun; Adelia Putri; Adinda Aurel; Aghniyatuz Zahwa Sholeha; Ahmad Fauza (MAN 4 Kota Pekanbaru, 2026)
This study aims to determine and analyze the influence of service quality and price on consumer loyalty at Harmony Hairstyle Stabat. The increasingly competitive barbering service business requires service providers to maintain consumer loyalty through appropriate service strategies and pricing. This type of research is associative research with a quantitative approach. The population in this study were all consumers of Harmony Hairstyle Stabat, with a sample size of 70 respondents taken using the Random Sampling technique. The data collection technique used a questionnaire that had been tested for validity and reliability. Data were analyzed using the multiple linear regression method through SPSS software. The results of the research partially (t-test) show that service quality has a positive and significant effect on consumer loyalty, and price has a positive and significant effect on consumer loyalty. Simultaneously (F-test), service quality and price have a significant effect on consumer loyalty at Harmony Hairstyle Stabat. The coefficient of determination value indicates that consumer loyalty is strongly influenced by both variables, while the rest is explained by other factors outside of this study.